Women's development group leaders' promotion of maternal, neonatal and child health care in Ethiopia: a cross-sectional study - Fisseha Ashebir; Araya Abrha Medhanyie; Afework Mulugeta; Lars Åke Persson; Della Berhanu (Taylor & Francis Group, 2020)
Background Women's development group leaders are volunteer community health workers in Ethiopia who, among other duties, promote health and prevention of diseases. They link and extend essential health services from health posts to households. Objective To assess the characteristics, knowledge, and practice of women's development group leaders in the field of maternal, neonatal, and child health care. Method This study used a cluster-sampled cross-sectional survey conducted from December 2016 to February 2017 in four regions of Ethiopia: Oromia, Amhara, Tigray and Southern Nations, Nationalities and Peoples. One of the volunteers, who was available at the time of the survey, was included from each cluster. A total of 187 women's development group leaders participated in this quantitative study. Result Close to half of the women's development group leaders were illiterate. The leaders had a wide variation in the number of women in their groups. Two-thirds had received some training during the last year, covering a broad range of health topics. Their knowledge of maternal, newborn, and child health was relatively low. Two-thirds had monthly contact with health extension workers. Around half had interacted with other local stakeholders on maternal and child health matters during the last three months. Two-thirds had visited pregnant women, and half had made home visits after delivery in the previous quarter. Activities regarding sick newborns and under-five children were less frequent. Conclusion The women leaders were given a wide range of tasks, despite having a low educational level and receiving training through brief orientations. They also showed limited knowledge but had a relatively high level of activities related to maternal health, while less so on neonatal and child health.